PENINGKATAN AKURASI DIMENSI DAN TINGKAT KEKERASAN PADA FILLAMENT ESTEEL DENGAN PENDEKATAN METODE TAGUCHI - Apriansyah, Icvan; Zamheri, Ahmad; Arifin, Fatahul (Politeknik Negeri Sriwijaya, Indonesia, 2021)
3D Printing is a new breakthrough in the world of technology. This breakthrough is very popular in all parts of the world, especially among academia and industry. The emergence of 3D Printing technology is very influential in several industrial fields, especially from an economic perspective. Rapid prototyping of mechanical components with techniques and low production volumes to quickly produce prototypes. The purpose of this study was to determine the dimensional accuracy of the 3D printer process using different parameters. In the testing process using the Digimatic Vernier Caliper Mitutoyo Absolute test tool, which uses an accuracy of 0.02 mm and the ALBERT GNHEM HORGEN hardness test tool and the Mitutoyo PJ-A3000 Projector Profile. The test data were analyzed using the Taguchi method.